Childhood Abuse, Intimate Partner Violence and Risk of Migraine Among Pregnant Women: An Epidemiologic Study - Gelaye, Bizu (2016)
Objective To examine the independent and joint associations of childhood abuse and intimate partner violence with migraine among pregnant women. Background Childhood abuse and intimate partner violence have each been associated with migraine headaches in previous studies, but these associations have not been explored among pregnant women. Methods A cross-sectional study was conducted among a cohort of 2970 pregnant women attending prenatal clinics in Lima, Peru. History of childhood abuse (ie, physical or sexual abuse) was assessed using the Childhood Physical and Sexual Abuse Questionnaire. Intimate partner violence (IPV) was assessed using the World Health Organization questionnaire. Migraine classification (including migraine and probable migraine) was based on International Classification of Headache Disorders (ICHD)-III beta criteria. Multivariable logistic regression analyses were performed to estimate odd ratios (OR) and 95% confidence intervals (95% CI). Results The prevalence of any migraine was 33.5% while approximately 70% of participants reported a history of childhood abuse and 36.7% a history of IPV. Women with a history of any childhood abuse had a 38% increased odds of any migraine compared to women with no history of childhood abuse (OR = 1.38; 95% CI 1.15-1.64). The odds of migraine increased with increasing numbers of experienced childhood abuse events (Ptrend < .001). Additionally, after adjusting for confounders women with a history of IPV had a 43% increased odds of any migraine as compared to women without intimate partner violence (OR = 1.43; 95%CI 1.02-2.02). Women with a joint positive history of childhood abuse and IPV, as compared with the reference group, had a 88% increased odds of migraine (aOR = 1.88, 95%CI: 1.51-2.35). Conclusion Childhood abuse and IPV are associated with increased odds of migraine in pregnant women. Our findings highlight the importance of screening for abuse among pregnant migraineurs to help guide treatment strategies.